Propósito da Santa Sé de não tocar no Padroado (1923)
This 1923 diplomatic dispatch, dated 27 January and sent from Rome by J. P. to the Portuguese Minister of Foreign Affairs, constitutes a confidential report on ecclesiastical and political tensions surrounding Portugal’s Padroado rights in India. The document records discussions held with Monsignor Borgongini and the Cardinal Secretary of State regarding sustained campaigns against the Portuguese patronage system in Indian territories, particularly Goa, Daman, and Cochin. Drawing on information provided by Portuguese prelates, including the Archbishop of Goa and the Bishops of Daman and Cochin, the author characterises the opposition as tendentious and malevolent, driven by both indigenous and British actors—ecclesiastical and lay—and supported by formal complaints submitted to the Vatican, often through the British minister. The correspondence highlights the volume of anti-Padroado petitions and press coverage forwarded to the Holy See, calling for abolition or radical reform. A key allegation addressed is Portugal’s alleged failure to meet financial obligations to mission personnel, which the author acknowledges has occurred due to administrative delays, leading to public embarrassment. Despite these challenges, the author affirms that the Holy See reaffirmed Portugal’s rights, with both the Cardinal Secretary and Monsignor Borgongini explicitly stating no intention to alter the status quo—a position aligned with Pope Benedict XV’s earlier assurances. The dispatch concludes with an assessment that while the campaign will likely persist, vigilant defence of the Padroado may render it ineffective.
Keywords: Administrative Delays; Anglo-Portuguese Relations; Anti-Padroado Campaign; Cardinal Secretary Of State; Catholic Church in India; Colonial Administration; Colonial Patronage; Confidential Report; Diplomatic Dispatch; Ecclesiastical Extension; Financial Obligations; Goa Daman Cochin; Historical Documents; Holy See Policy; Indigenous and British Opposition; Mission Personnel; Monsignor Borgongini; Political Conflict in India; Portuguese Padroado Rights; Portuguese Prelates; Radical Reform Demands; Sustained Opposition; Tendentious Criticism; Transcription; Vatican Correspondence; Vatican Stance